Transmissibility and Persistence of the Plasmid-Borne Mobile Colistin Resistance Gene, mcr-1, Harbored in Poultry-Associated E. coli - Hassan Al Mana; Alreem A. Johar; Issmat I. Kassem; Nahla O. Eltai (MDPI AG, 2022)
Colistin, a last-resort antibiotic, is used to treat infections caused by multi-drug-resistant Gram-negative bacteria. Colistin resistance can emerge by acquiring the mobile colistin gene, mcr-1, usually plasmid borne. Studies on mcr-1 and its transmissibility are limited in the Middle East and North Africa (MENA) region. Here, we investigated the occurrence of mcr-1 in 18 previously collected Escherichia coli isolates collected from chicken samples in Qatar; whole-genome sequencing was performed to determine the location (plasmid-borne and chromosomal) of mcr-1 in the isolates. Additionally, we assessed the transmissibility of plasmid-borne mcr-1 and its cost on fitness in E. coli biofilms. Our results showed that the E. coli isolates belonged to different sequence types, indicating that mcr-1 was occurring in strains with diverse genetic backgrounds. In silico analysis and transformation assays showed that all the isolates carried mcr-1 on plasmids that were mainly IncI2 types. All the mcr-1 plasmids were found to be transmissible by conjugation. In biofilms, a significant reduction in the number of CFU (≈0.055 logs CFU/mL) and colistin resistance (≈2.19 log CFU/mL) was observed; however, the reduction in resistance was significantly larger, indicating that the plasmids incur a high fitness cost. To our knowledge, this is the first study that investigates mcr-1 transmissibility and persistence in Qatar. Our findings highlight that mcr has the potential to spread colistin resistance to potentially disparate strains and niches in Qatar, posing a risk that requires intervention.